ANALISIS MENUMBUHKAN MINAT BERWIRAUSAHA PESERTA DIDIK OLEH GURU DI SMK SUPM KALBAR - Yulanda, Yulanda; Genjik, Bambang; Basri, Muhammad (Jurnal Pendidikan dan Pembelajaran Khatulistiwa (JPPK), 2024)
This research aims to determine teachers' efforts to foster students' interest in entrepreneurship, supporting factors and inhibiting factors to foster students' interest in entrepreneurship. This type of research uses descriptive methods and the approach used by researchers is a qualitative approach. The presence of researchers is the main tool in collecting data and the research participants in this research are entrepreneurship teachers and students. The data collection techniques used in this research were interviews and documentation. The analysis technique in this research uses data reduction, data presentation, and drawing conclusions. The results of this research are the efforts of entrepreneurship subject teachers to foster interest in entrepreneurship in students at the Pontianak SUPM Vocational School, namely motivating students, giving students examples of inspiring and successful stories in entrepreneurship, and practical activities. The supporting factor in fostering students' interest in entrepreneurship at SMK SUPM KALBAR is the entrepreneurial practice activities carried out every semester. Factors inhibiting the obstacles faced in fostering students' interest in entrepreneurship at the SUPM KALBAR Vocational School, namely the presence of students during class hours, students at the Vocational School are required to live in a dormitory so their dormitory is still in the same area as the classroom, sometimes they are too lazy to go to class, participant response Students who are lacking in learning, adequate infrastructure but students who are less enthusiastic about receiving lessons are one of the obstacles in increasing interest in entrepreneurship.